Structure-guided discovery of potent and oral soluble epoxide hydrolase inhibitors for the treatment of neuropathic pain - Fangyu Du; Ruolin Cao; Lu Chen; Jianwen Sun; Yajie Shi; Yang Fu; Bruce D. Hammock; Zhonghui Zheng; Zhongbo Liu; Guoliang Chen (Elsevier, 2022)
Soluble epoxide hydrolase (sEH) is related to arachidonic acid cascade and is over-expressed in a variety of diseases, making sEH an attractive target for the treatment of pain as well as inflammatory-related diseases. A new series of memantyl urea derivatives as potent sEH inhibitors was obtained using our previous reported compound 4 as lead compound. A preferential modification of piperidinyl to 3-carbamoyl piperidinyl was identified for this series via structure-based rational drug design. Compound A20 exhibited moderate percentage plasma protein binding (88.6%) and better metabolic stability in vitro. After oral administration, the bioavailability of A20 was 28.6%. Acute toxicity test showed that A20 was well tolerated and there was no adverse event encountered at dose of 6.0 g/kg. Inhibitor A20 also displayed robust analgesic effect in vivo and dose-dependently attenuated neuropathic pain in rat model induced by spared nerve injury, which was better than gabapentin and sEH inhibitor (±)-EC-5026. In one word, the oral administration of A20 significantly alleviated pain and improved the health status of the rats, demonstrating that A20 was a promising candidate to be further evaluated for the treatment of neuropathic pain.